2018
DOI: 10.1177/0300060518801455
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic uterine artery embolization in second-trimester pregnancy termination with complete placenta previa

Abstract: Objective This study was performed to assess whether prophylactic uterine artery embolization (UAE) is beneficial for second-trimester abortion with complete placenta previa (CPP). Methods Patients with CPP who underwent second-trimester pregnancy termination by labor induction with or without UAE from January 2010 to January 2018 were retrospectively reviewed. In total, 25 patients were eligible for analysis. The primary outcomes were the abortion success rate and bleeding volume, and the secondary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…[ 13 ] Studies have shown that preventive uterine artery embolization does not significantly improve the outcomes of pregnancy termination in patients with complete placenta previa, but increases the risk of complications and leads to a longer hospital stay. [ 14 ] Therefore, the application of vascular interventional techniques in obstetrics is a complicated and expensive procedure that also needs additional personnel and equipment. The necessity and safety of vascular interventional techniques need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Studies have shown that preventive uterine artery embolization does not significantly improve the outcomes of pregnancy termination in patients with complete placenta previa, but increases the risk of complications and leads to a longer hospital stay. [ 14 ] Therefore, the application of vascular interventional techniques in obstetrics is a complicated and expensive procedure that also needs additional personnel and equipment. The necessity and safety of vascular interventional techniques need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…How to prevent and deal with prenatal hemorrhage is the key. In recent years, the combination of UAE and conventional medical or instrument labor induction methods has become a new treatment scheme widely studied in clinical practice [7,9,28] . Prophylactic UAE before curettage in patients with cesarean scar pregnancy is safe and effective [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic UAE before curettage in patients with cesarean scar pregnancy is safe and effective [7] . However, whether to use emergency or prophylactic UAE for termination of mid-pregnancy with placental previa still remains debated [9,28] . He et al [9] analyzed 85 cases with complete placenta previa for termination of second-trimester pregnancy, in which 20 cases were treated with cesarean delivery, 30 cases were treated with Mifepristone+Rivanl+UAE, and 35 patients were induced by Mifepristone+Rivanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UAE with minimal invasion has been widely used in the field of gynecology and obstetrics to control hemorrhages, including caesarean scar pregnancy [10] , postpartum hemorrhage [11] by caesarean delivery or vaginal delivery. Whether or not to use prophylactic UAE for termination in the second trimester for pregnant women with CPP remains debated [7,10] .…”
Section: Discussionmentioning
confidence: 99%